Autoantibody profiling in APS. (October 2014) - Roggenbuck, D; Somma, V; Schierack, P; Borghi, MO; Meroni, PL
The international consensus for the classification of antiphospholipid syndrome (APS) requires clinical and laboratory criteria to be considered at an equal level for diagnosing APS. Thus, detection of antiphospholipid antibodies (aPL) being a hallmark of APS has been the object of intensive investigation over the past 40 years. However, appropriate detection of aPL still remains a laboratory challenge due to their heterogeneity comprising autoantibodies reactive to different phospholipid-binding plasma proteins, such as beta-2 glycoprotein I (β2GPI) and prothrombin. The relevance of aPL interacting with phospholipids other than cardiolipin (CL, diphosphatidylglycerol), such as phosphatidylserine (PS), remains elusive with regard to the diagnosis of APS. Recently, the concept of aPL profiling has been introduced to assess the risk of thrombotic complications in patients with APS. New assay techniques, apart from enzyme-linked immunosorbent assays (ELISAs) recommended by the international consensus for the classification of APS, have been proposed for multiplexing of aPL testing. Line immunoassays (LIAs) employing a novel hydrophobic solid phase for the simultaneous detection of different aPL seem to be an intriguing alternative. We evaluated a novel multiplex LIA employing a hydrophobic membrane coated with different phospholipid (PL)-binding proteins or PLs. The performance characteristics of this new multiplexing assay technique demonstrated its usefulness for aPL profiling.